Correlación entre el examen de admisión y el rendimiento en el primer año de la carrera Enseñanza de la Matemática en la UNA - Chaves, Edwin (2008)
This article analyzes the relationship between the admission exams from the Universidad Nacional de Costa Rica (UNA) and the performance of students during their first two courses of specialization in the field of Teaching Mathematics.In this analysis, the following variables were considered: individual result at the admission exam, average performance during high school and during the first two Mathematics courses of the career. To determine the relation between the variables, Pearson’s correlation coefficient was used.The results reveal that the different modules of the admission exams show a low correlation with the performance in both courses. Therefore, the research concluded that the current process of selection of students, based on an admission exam, is not a tool that can be considered adequate to detect the previous knowledge to guarantee the success in the university career